Causes of Problems Students Face While Learning Turkish as a Foreign Language: The Case of Kazakhstan - Cemal Ozdemir (Foxton Books, 2018)
This study is designed to determine the causes of the problems that Kazakh students face when learning Turkish as a foreign language. The study group consists of 40 students at A2 level who studied Turkish at a private university in Kazakhstan during the 2016-2017 academic year. A Likert-type questionnaire consisting of 27 items was used to collect the data. The survey, which was organized in four parts; reading, speaking, listening and writing, included expressions regarding the causes of problems students are experiencing. The obtained data was analyzed by MS Excel and SPSS programs. Students' opinions about the causes of the problems in learning Turkish language were presented as graphs and t-test analysis was conducted to reveal gender differences. As a result, it has been seen that the students definitely participated in some of the expressions which were determined as the cause of problems they encounter and they did not participate in some of the identified causes. However, it has emerged that students are often neutral against the identified problems. On the other hand, while boys and girls have similar opinions about the causes of problems in reading and speaking, it has been determined that girls statistically agreed more than boys about the identified causes of problems in listening and writing.